1965
DOI: 10.1161/01.res.16.1.11
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Arrhythmias Following Condenser Discharges Led Through an Inductance:

Abstract: With the technical assistance of 1. Blaiek, M. Rabl and E. Sladkova and the statistical evaluation of Ing. 1. Roth MethodsThe present experiments were performed under pentobarbital anaesthesia (20 to 40 mgAg body \vt iv) on mongrel dogs, weighing from 20 to 25 kg. The electronic device for synchronizing the condenser discharge with selected phases of the electrocardiogram has been described previously. 1 The methods, in general, were also the same as before except that an inductive resistance (inductance 0.29 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1966
1966
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…• The efficacy of various types of transthoracic shocks in reversing ventricular fibrillation and other cardiac arrhythmias has been extensively studied by numerous investigators (1)(2)(3)(4)(5)(6)(7)(8)(9). Because the character of the shocks delivered by the conventional or commercial apparatus used in these studies could be varied in only a very restricted fashion, the studies were more useful as a guide to immediate clinical application than for the elicitation of fundamental information concerning the defibrillation process.…”
Section: Introductionmentioning
confidence: 99%
“…• The efficacy of various types of transthoracic shocks in reversing ventricular fibrillation and other cardiac arrhythmias has been extensively studied by numerous investigators (1)(2)(3)(4)(5)(6)(7)(8)(9). Because the character of the shocks delivered by the conventional or commercial apparatus used in these studies could be varied in only a very restricted fashion, the studies were more useful as a guide to immediate clinical application than for the elicitation of fundamental information concerning the defibrillation process.…”
Section: Introductionmentioning
confidence: 99%
“…Mackay and Leeds (11), on the basis of a study of dogs weighing 8-12 kg, showed that electrical energy was the appropriate electrical parameter for indicating the requirement for defibrillation. Others (12)(13)(14)16) have proposed that the current that flows is a better descriptor for the electrical dose required for defibrillation. Without arguing the issue of the superiority of current over energy for specifying the dose for ventricular defibrillation, Fig.…”
mentioning
confidence: 99%
“…In 1957, Bohumil Peleška, from Prague, Czechoslovakia, reported on both direct and transthoracic use of DC shock for defibrillation purposes 24. He constructed his own DC defibrillator, modifying Gurvich’s design by including an iron core in the inductor,25 and is credited with improving the procedure of cardioversion by using lower voltage and describing the effects of DC shock. Thus, the original work on biphasic defibrillation waveforms and DC cardioversion and defibrillation had originated initially in the East.…”
Section: Historymentioning
confidence: 99%